Pembelajaran Puisi Selaras Abad 21 - Dipa Nugraha (Jurnal Pendidikan Edutama, 2023)
Abstract:  Poetry learning that is adaptive to the needs of students in the 21st century has not been much discussed in Indonesia. This article aims to review several important matters related to poetry learning in the 21st century. This article also discusses the concepts of “physical structure” and “inner structure” coined by Waluyo which are very dominant in poetry learning in Indonesia in the context of the potential for continuing their use in poetry learning in the 21st century at high school and college levels. This article is a literature review articlearticle by library research method through careful reading of books or articles that are relevant to the topic of this article was conducted. The literature review came to the conclusion that appreciation theory or poetry studies with the terms "physical structure" and "inner structure" from Waluyo should not continue to be taught as if it were the only theory. There are several concepts of poetry appreciation or study that can be used as alternatives to be taught in poetry learning in Indonesian high schools and universities. As for poetry learning in the 21st century, it must be realized that it cannot avoid issues such as multiculturalism, intertextuality, digitalization and the use of artificial intelligence, transmediality, intermediality, and multimodality. Keywords:  poetry learning, physical structure, inner structure, 21st century poetry learning Abstrak: Pembelajaran puisi yang adaptif dengan kebutuhan peserta didik pada abad 21 belum banyak dibicarakan di Indonesia. Artikel ini bertujuan mengulas beberapa hal penting terkait dengan pembelajaran puisi abad 21. Selain itu, artikel ini juga membahas konsep “struktur fisik” dan “struktur batin” milik Waluyo yang sangat dominan di dalam pembelajaran puisi di Indonesia dalam konteks potensi penerusan penggunaannya di dalam pembelajaran puisi abad 21 pada jenjang SMA dan perguruan tinggi. Artikel ini adalah artikel kajian pustaka dengan menerapkan metode riset kepustakaan melalui pembacaan cermat buku atau artikel yang relevan dengan topik artikel ini. Kajian pustaka yang dilakukan sampai pada kesimpulan bahwa teori apresiasi atau kajian puisi dengan pasangan istilah “struktur fisik” dan “struktur batin” dari Waluyo sebaiknya tidak terus diajarkan seolah-olah sebagai satu-satunya teori. Ada beberapa konsep apresiasi atau pengkajian puisi yang bisa dijadikan alternatif untuk diajarkan dalam pembelajaran puisi di SMA dan perguruan tinggi di Indonesia. Adapun pembelajaran puisi abad 21 harus disadari tidak bisa menghindar dari isu-isu seperti multikulturalisme, intertekstualitas, digitalisasi dan penggunaan kecerdasan buatan, transmedialitas, intermedialitas, dan multimodalitas.  Kata Kunci: pembelajaran puisi, struktur fisik, struktur batin, pembelajaran puisi abad 21